The potential function of microRNAs as biomarkers and therapeutic targets in multiple myeloma - Zhu, Bingying (Oncol Lett, 2018)
Multiple myeloma (MM), accounting for ~1% of all types of human cancer and 13% of all hematological malignancies, is characterized by the malignant proliferation of monoclonal plasma cells (PCs) in the bone marrow. MM leads to end stage organ impairment, including bone lesions, renal dysfunction, hypercalcemia and anemia. So far, the specific pathogenesis of MM remains unclear and no early-stage sensitive biomarker of MM has been well characterized. Furthermore, treating MM is difficult, as the majority of patients eventually relapse or become refractory following treatment using presently available methods. To date, a number of studies have demonstrated that microRNAs (miRNAs) may serve crucial functions in the progression of numerous cancers, including MM. During the tumorigenesis and pathogenesis of MM, there are multiple carcinogenic events that involve the pernicious transformation from normal to malignant PCs. miRNAs, as oncogenes or tumor suppressors, regulate MM progression-related signaling pathways. In the present review, the up-to-date preliminary basic studies and associated clinical works on the underlying mechanisms of aberrant miRNA profiling in MM have been summarized, including an evaluation of its value as a potential biomarker and a novel therapeutic strategy for MM.